A study of emotional intelligence and coping strategies among UiTM medical imaging students / Angeline Amyliana Anuar, Shahridah Kassim and Ann Erynna Lema Thomas Sudin - Anuar, Angeline Amyliana; Kassim, Shahridah; Thomas Sudin, Ann Erynna Lema (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Emotional intelligence is essential in coping with stressful situation. Coping may be also related to emotional aptitude, empathy and self-monitoring and stress duration. Thus, this study was to investigate the relationship between emotional intelligence and coping strategies among medical imaging students at Universiti Teknologi Mara (UiTM) Puncak Alam. The samples involved in this study were 207 medical imaging students from diploma and degree programmes. A survey was carried out using the adopted version of Schutte Self-Report Emotional Intelligence Test (SSEIT) and Coping Strategies Inventory (CSI). The result of this study revealed that 79.7% of 207 students had moderate level of emotional intelligence. The results also showed that emotional intelligence had a positive significant relationship with four subscales of engagement coping strategies including problem-solving, cognitive restructuring, express emotion and social contact (p < 0.001).Among these subscales, cognitive restructuring showed moderate relationship (r=0.525) while the other subscales showed weak relationship (r < 0.5). This study reveals that students with moderate to a high level of emotional intelligence tend to use engagement coping strategies.